2020
DOI: 10.1212/nxg.0000000000000486
|View full text |Cite
|
Sign up to set email alerts
|

Delineating the phenotypic spectrum of sulfite oxidase and molybdenum cofactor deficiency

Abstract: ObjectiveTo define the phenotypic spectrum of isolated sulfite oxidase (ISOD) and molybdenum cofactor deficiency (MoCD), aiming to promote timely diagnosis and assist in future clinical trial design.MethodsWe analyzed clinical, radiographic, biochemical, and genetic data from 146 patients reported in the literature.ResultsWe stratified patients into 2 phenotypic subgroups based on clinical and radiographic characteristics. In the first (Class I), patients presented early in life (age 1–50 days) with acute onse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(45 citation statements)
references
References 35 publications
1
44
0
Order By: Relevance
“…Other clinical features of ISOD include ectopia lentis and increased urinary excretion of thiosulfate, sulfite, and S-sulfocysteine (Edwards et al 1999). In a recent review of 47 cases, MRI abnormalities like herein were identified in all cases (Eichler et al 2006;Bindu et al 2017;Claerhout et al 2018;Misko et al 2020). There is currently no effective treatment for ISOD.…”
Section: Genomic Analysesmentioning
confidence: 79%
“…Other clinical features of ISOD include ectopia lentis and increased urinary excretion of thiosulfate, sulfite, and S-sulfocysteine (Edwards et al 1999). In a recent review of 47 cases, MRI abnormalities like herein were identified in all cases (Eichler et al 2006;Bindu et al 2017;Claerhout et al 2018;Misko et al 2020). There is currently no effective treatment for ISOD.…”
Section: Genomic Analysesmentioning
confidence: 79%
“…10 Recently published articles have reviewed MoCoD patients reported in the literature and delineated the phenotypic spectrum: a narrow phenotypic spectrum across patients in the early-onset form with severe neurological impairment and a pattern of global injury susceptibility of the forebrain and cerebellum may be driven mainly by genotype; a wider phenotypic spectrum in patients with the late-onset form ranged from static neurologic symptoms to progressive neurological involvement with periodic decompensation in function, even in adulthood, and the pattern of selective injury susceptibility of the basal ganglia and cerebellum may be driven by a complex interaction of genotype, external environment triggers, and developmental context. 5,8 In addition, the residual enzymatic activity of sulfite oxidase might contribute to the phenotypes. 5 One of the limitations of this study was the lack of available data on sulfite oxidase activity, so it was not possible to draw definitive conclusions from our results.…”
Section: Discussionmentioning
confidence: 99%
“…5,8 In addition, the residual enzymatic activity of sulfite oxidase might contribute to the phenotypes. 5 One of the limitations of this study was the lack of available data on sulfite oxidase activity, so it was not possible to draw definitive conclusions from our results. Further studies are needed to investigate the correlations among phenotype, genotype, sulfite oxidase activity, and environmental triggers in patients with MoCoD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Clinically, ISOD and MoCD present with the same symptoms and complications caused by sulphite accumulation, except those patients with MoCD can, in addition, develop nephrolithiasis due to impaired XOR activity. 18 MoCD and ISOD are ultra-rare diseases, with published reports of fewer than 200 patients with MoCD [19][20][21] and fewer than 100 with ISOD. 22 (MoCD-B), caused by MOCS2 variants 23 or, rarely, MOCS3 mutations.…”
Section: Clinical Presentation Of Molybdenum Cofactor Deficiencymentioning
confidence: 99%